Thinking about the event. An approach to Slavoj Žižek’s traumatic proposal - Sánchez Quintana, Esteban Andrés (2020)
The purpose of this article is to address some aspects of the conceptual category “event”, following Slavoj Žižek’s perspective. The structure of the text is as follows: To begin, the aim is to define, redefine and frame the concept. Next, an attempt will be made to account for how this phenomenon occurs in relation to the human psyche. Finally, think with the Slovenian philosopher, who is understood by the “traumatic” condition of the event.